Foreign versus local firms: implications for environmental sustainability - Balasubramanian, Sreejith; Shukla, Vinaya (Benchmarking : an international journal, 2020)
PurposeManaging environmental consequences while sustaining economic development necessitate strong commitment and participation of all firms across sectors. However, the environment-related role of foreign and local firms is unclear from previous research. With increasing trade liberalization and entry of foreign firms, this question has become particularly relevant. The purpose of this paper is to contrast the roles and contributions of foreign and local firms from an environmental sustainability perspective.Design/methodology/approachUsing data collected through a structured survey (395 responses) and semi-structured interviews (19 numbers) from the United Arab Emirates (UAE) construction sector (research setting), the study analyses and understands the hypothesized differences between foreign and local firms on three key environmental sustainability aspects: the extent of environmental practices implementation, the strengths/influences of drivers and barriers affecting the implementation, and the environmental, cost-related, and organizational performance benefits derived.FindingsForeign firms were found to implement environmental practices to a greater extent, have a greater internal drive to implement these practices, and face lower barriers to implementation than local ones. Local firms though were found to be not far behind foreign ones with regards to the environmental, cost-related, and organizational performance benefits derived.Practical implicationsFindings from the study are expected to help policymakers and practitioners develop policies/interventions that ensure all firms irrespective of their nature of ownership contribute equitably to environmental sustainability.Originality/valueThis study is arguably the first comprehensive attempt to understand how various environmental sustainability aspects are perceived and performed by local and foreign firms.